Unseen academicals : a novel of Discworld - Pratchett, Terry (Pratchett, Terry. Discworld series (New York, N.Y.), 2009)
The wizards of Unseen University in the ancient city of Ankh-Morpork must win a football match, without using magic, so they're in the mood for trying everything else. As the match approaches, four lives are entangled and changed forever.